Kendala Penggunaan Google Classroom Pada Siswa Kelas III SDN 2 Menyali Dalam Persepektif Komunikasi Interpersonal - I Gede Teguh Heriawan (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2022)
During the Covid-19 pandemic requires that every component of education and communication carry out the online learning by using various educational platforms such as Google Classroom as the media. So, the purpose of this research is to identify the problems encountered by the third grade students of elementary school Number 2 Menyali with a frequency of 30 students. The sampling was carried out by applying the saturated sampling technique, which was the whole of the population members who were used as research samples. Data collection in this research was obtained through an instrument in the form of questionnaire consisting of 4 indicators with 9 questions. The Guttman scale was used as an instrument in this research with alternative answers of “yes” and “no”. Then, the data that had been obtained were re-analyzed with quantitative descriptive anyalysis and qualitative descriptive analysis. Quantitative descriptive analysis that is done by determining the average percentage of each dimension of the research instrument which is then categorized into a percentage category table from each research instrument dimension which is then categorized into a percentage category table. Followed by use of descriptive qualitative analysis, that is describes the percentage result data and relates it to the results of previous studies. Based on the results of the imaging, it is found that there are four main problems in the process of using google classroom including the lack of student adaptability, low ability to use applications, lack of availability of devices and low ability to understand material during learning activities which in communication science are expressed as noise.